The Freedom of Information Act and the Race Toward Information Acquisition - Gargano, Antonio; Rossi, Alberto G.; Wermers, Russ (Review of Financial Studies, 2017)
We document a little-known source of information exploited by sophisticated institutional investors: the Freedom of Information Act (FOIA), a law that allows for the disclosure of previously unreleased information by the U.S. Government. Through FOIA requests, we identify several sophisticated institutional investors, chiefly hedge funds, that request information from the FDA. We explore the type of information commonly requested by funds and the types of firms that are targets of FDA-FOIA requests and show that FOIA requests allow these investors to generate abnormal returns. Thus, we illustrate a detailed mechanism through which costly information becomes incorporated into market prices. Received April 15, 2015; editorial decision April 16, 2016 by Editor Itay Goldstein.